Receptor for advanced glycation endproducts signaling cascades are activated in pancreatic fibroblasts, but not in the INS1E insulinoma cell line: Are mesenchymal cells major players in chronic inflammation?. Issue 5 (2nd September 2016) - Tago, Kazuma; Inoue, Ken-ichi; Ouchi, Motoshi; Miura, Yoshikazu; Kubota, Keiichi
ABSTRACT: The receptor for advanced glycation endproducts (RAGE) is a pattern recognition receptor that plays an important role in natural immunity. It is suggested that mesenchymal cells are the major players during inflammation. Previously, we reported that advanced glycation end products (AGE), known to be one of the ligands of RAGE, inhibited glucose-induced insulin secretion from ex vivo pancreatic islets, although the mechanism responsible remains largely unknown. In the present study, we examined the cascades operating downstream from RAGE using the insulinoma cell line INS1E and primary-cultured pancreatic fibroblasts as in vitro models for parenchymal (β) cells and mesenchymal cells, respectively. Phosphorylation of c-jun N-terminal kinase, inhibitor of nuclear factor κB kinase, and nuclear factor κB was stimulated by AGE or high mobility group binding 1 (HMGB1) in pancreatic fibroblasts, whereas no such effect was observed in INS1E cells. Expression of the Ccl5, Il-6, and Il-1b genes was increased by AGE/HMGB1 in fibroblasts, but not in INS1E cells. On the other hand, AGE inhibited the secretion of insulin from ex vivo pancreatic islets, and this effect was ameliorated by MK615, a Japanese apricot extract used as an anti-inflammatory agent. Glucose-induced insulin secretion from INS1E cells was not affected by direct administration of AGE/HMGB1, but was inhibited by fibroblast-conditioned medium. These results suggest that AGE suppresses glucose-induced insulin secretion from pancreatic islets through indirect mesenchymal RAGE signaling.